Case Report: Reconstruction of Medialis Malleolus (1/4 of the Ankle Joint) After Resection of Distal Tibia Tumor With an Uncemented Three-Dimensional-Printed Prosthesis - Wang, Shang; Luo, Yi; Zhang, Yuqi; Wang, Yitian; Zheng, Chuanxi; Tu, Chongqi; Zhou, Yong (Frontiers in Surgery, 2022)
Introduction: Some patients presented with a distal tibial tumor that only invaded a small area of bone in the medial malleolus. There have been no previous cases in which only the medial or lateral malleolus was removed and reconstruction was complete. Our paper describes our attempt to reconstruct the medial malleolus (1/4 of the ankle joint) after resection of a distal tibial tumor with an uncemented three-dimensional (3D)-printed prosthesis. Case description: A 39-year-old man presented with a lump in the right medial malleolus, and biopsy results suggested fibrosarcoma. To preserve the patient's normal bone and function, we only removed the medial malleolus and reconstructed the ankle joint using a personalized 3D-printed prosthesis. The patient had no complications other than necrosis of the skin flap that covered the wound. The patient recovered well after undergoing an additional skin flap transfer. Follow-up at 7 months and again at 3 years after surgery showed good ankle function and stability, with no pain or complications. Conclusion: The 3D-printed partial ankle prosthesis had a good matching degree, strength, and osseointegration ability, and had few complications. The patient achieved satisfactory ankle function and stability. However, a longer follow-up period is needed, and more research is required to confirm the efficacy of the prosthesis.